Assessment of distress in patients visiting pain and palliative out patient department of a tertiary care hospital in Assam - Borkotoky, Priyakhi; Deka, Arun; Dakua, Dipankar; Das, Shantana (International Journal of Research in Medical Sciences, 2022)
Background: Distress is a multifactorial entity seen in patients battling with cancer. It is under-reported and under-managed posing a hurdle in providing holistic patient care. It has a negative effect on the treatment and treatment adherence in cancer patients. Methods: A cross- sectional study was done in the pain and palliative outpatient clinic of State Cancer Institute, Guwahati, Assam. About 250 patients were screened for distress using a questionnaire consisting of national comprehensive cancer network (NCCN) distress thermometer (DT) and problem list over a span of 4 months after obtaining due consent. They were asked to mark their level of distress and the contributing factors for distress as enlisted in the NCCN DT problem list. Chi square test and Mann Whitney test were used to analyze statistical significance. Results: The distress levels were assessed based on the effects of the disease, treatment and other demographic variables and possible causes contributing to distress were determined. It was noted that out of 250 patients screened (n=250), 88 (35.2%) reported a distress score of 4 while 79 (31.6%) reported with a score of 6. Nature of the disease and current treatment received by the patient was significantly associated with distress while age, marital status and sex was not. Amongst physical, emotional and practical problems leading to distress, pain (45.2%), worry (49.2%) and transportation issues (45.1%) respectively were significantly reported as primary causes of distress. Conclusions: NCCN DT in an effective tool for assessment of distress in cancer patients of Assam. It helps in identification of probable causes of distress which aids in holistic patient care.